Power And Oppression In The Novels Of Buchi Emecheta - et. al., N. Sinthuja, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Oppression can be defined as any cruel or unjust treatment upon anyone for a prolonged period. It can be any form of abuse which varies from individual to a large community. It is mainly a tyranny where people show their cruel, unreasonable control and power upon others. This system of oppression is sometimes institutional which affects the whole clan of people. In such cases people have a long history deeply rooted in their culture. Throughout the history we could see women especially black women are subjected to exploitation, gender discrimination, domestic violence, male chauvinism etc. Many women writers have discussed about all these abuse against women in their own society. One such women writer is Buchi Emecheta whose work revolves around women in the African culture. Her works not only investigate the aspects of women’s oppression but also mounts a protest against it. Her characters fight for social justice irrespective of all the gender based obstacles..